HUBUNGAN BEBAN KERJA DENGAN STRES KERJA PADA PERAWAT DI RUMAH SAKIT X - Ika Wahyu Apriyanti; Yogie Erlangga Haq (STIKes IMC Bintaro, 2019)
Preface Workload is not always become a cause of stress among nurses, it can be precipitating a stress if physical ability, knowledge and technical skill, and the availability of time are inadequate. Purpose of this study is to seek the correlation between workload and work stress among nurses at Medika hospital BSD. Methodological studyusing survey and cross sectional design method. Number of sampling are 82 respondents and the researcher using questioner as data collection tool.The study result showed the number of nurses who experienced high workload were 47 (58%), heavy work stress were 6 (17.6%) respondents and high workload with heavy work stress were 28 (59.6%) respondents.The conclusion of this study confirmed there is a correlation betwen workload and work stress among nurse at Medika hospital BSD. Data analysis was measured using chi-square test. Where at the significance of α 5%, the p value was 0.001. It is recommended for the hospital to put more concern on this correlation between workload and work stress among nurse by distributing the tasks in accordance with their level of education.